PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN BUDAYA ORGANISASI TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Ruri M Frista Sibuea; Dianwicaksih Arieftiara (Veteran Economics, Management, & Accounting Review, 2022)
This study aims to determine the effect of managerial ownership, institutional ownership, and organizational culture on the disclosure of Corporate Social Responsibility with the audit committee as a moderating variable. This study uses gender diversity as a measurement for organizational culture. The object of this research is mining and manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2021 with a total sample of 113 samples. The technique for analyzing the data in this study uses the classical assumption test regression model selection, multiple linear regression test, and hypothesis testing using STATA version 16. The results of the test show that (1) managerial ownership has a negative effect on Corporate Social Responsibility disclosure, (2 ) institutional ownership has a positive effect on the disclosure of Corporate Social Responsibility, (3) gender diversity has no effect on the disclosure of Corporate Social Responsibility, (4) the audit committee cannot moderate the effect of managerial ownership on the disclosure of Corporate Social Responsibility, (5) the audit committee cannot moderate the influence institutional ownership on the disclosure of Corporate Social Responsibility, (6) the audit committee can moderate the effect of gender diversity on the disclosure of Corporate Social Responsibility. Keywords: Managerial Ownership;  Institutional Ownership;  Organizational Culture;  Committee Audit;  Corporate Social  Responsibility Disclosure. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh kepemilikan manajerial, kepemilikan institusional, dan budaya organisasi terhadap pengungkapan Corporate Social Responsibility dengan komite audit sebagai variabel moderasi. Penelitian ini menggunakan diversitas gender sebagai pengukuran untuk budaya organisasi. Objek penelitian ini adalah perusahaan pertambangan dan manufaktur terdaftar di BEI periode 2018-2021 dengan total sampel sebanyak 113 sampel. Teknik untuk menganalisis data pada penelitian ini menggunakan uji pemilihan model regresi uji asumsi klasik, uji regresi linear berganda, dan uji hipotesisi dengan menggunakan STATA versi 16. Hasil dari pengujian diperoleh bahwa (1) kepemilikan manajerial berpengaruh negatif terhadap pengungkapan Corporate Social Responsibility, (2) kepemilikan institusional berpengaruh positif terhadap pengungkapan Corporate Social Responsibility, (3) diversitas gender tidak berpengaruh terhadap pengungkapan Corporate Social Responsibility, (4) komite audit tidak dapat memoderasi pengaruh kepemilikan manajerial terhadap pengungkapan Corporate Social Responsibility, (5) komite audit tidak dapat memoderasi pengaruh kepemilikan institusional terhadap pengungkapan Corporate Social Responsibility, (6) komite audit dapat memoderasi pengaruh diversitas gender terhadap pengungkapan Corporate Social ResponsibilityKata Kunci: Kepemilikan Manajerial; Kepemilikan Institusional; Budaya Organisasi; Komite Audit; Pengungkapan Corporate Social Responsibility.